2013
DOI: 10.1128/jvi.00620-13
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Specific Effects of TRIM5α rh RING Domain Functions on Restriction of Retroviruses

Abstract: T he replication of human immunodeficiency virus type 1 (HIV-1) is potently blocked in Old World monkeys at an early postentry step, prior to reverse transcription (1, 2). In 2004, TRIM5␣ was identified as the major host factor that mediates this block (3). Since this discovery, the TRIM5 proteins of multiple mammalian species have been characterized, and the range of restricted viruses has expanded to include a variety of retroviruses (lentiviruses, a betaretrovirus, a gammaretrovirus, and spumaviruses) (4-16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…This process required the E3 ubiquitin ligase activity of the RING domain of TRIM5α to facilitate the higher-order association of its dimers for capsid binding [47]. Our results also demonstrated that TRIM11 could lead to decreased HIV-1 reverse transcripts and that the RING domain was necessary for the inhibitory activity of TRIM11 during this step.…”
Section: Discussionsupporting
confidence: 55%
“…This process required the E3 ubiquitin ligase activity of the RING domain of TRIM5α to facilitate the higher-order association of its dimers for capsid binding [47]. Our results also demonstrated that TRIM11 could lead to decreased HIV-1 reverse transcripts and that the RING domain was necessary for the inhibitory activity of TRIM11 during this step.…”
Section: Discussionsupporting
confidence: 55%
“…Deletion of the coiled-coil region prevents stable binding of the retroviral CA protein (21), whereas the B-box promotes cooperative CA binding by mediating higherorder Trim5α self-association (30). Disruption or removal of the RING domain interferes with proteasome interactions, delaying the block in virus replication until after reverse transcription has occurred, but can also affect higher-order RF association (31).…”
mentioning
confidence: 99%
“…The RING domain of TRIM5α rh is an E3 ubiquitin ligase (Diaz-Griffero et al, 2006a; Kar et al, 2008; Kim et al, 2011; Langelier et al, 2008; Li et al, 2013; Lienlaf et al, 2011; Maegawa et al; Pertel et al, 2011; Yamauchi et al, 2008). The E3-ligase activity of TRIM5α is correlated to the ability of TRIM5α to block HIV-1 (Lienlaf et al, 2011).…”
mentioning
confidence: 99%